2016
DOI: 10.19044/esj.2016.v12n15p160
|View full text |Cite
|
Sign up to set email alerts
|

Uso De Un Polímero Hidrófilo A Base De Poliacrilamida Para Mejorar La Eficiencia En El Uso Del Agua

Abstract: As an alternative in search of new options to reduce overexploitation of groundwater that allow us to increase agricultural profitability in water scarce areas, the behavior of a commercial hydrophilic polymer based in polyacrylamide (PAM) Lluvia solida®, was analyzed by evaluating the polymer hydration capacity. The tests that we used showed that this polymer is capable of absorbing its own weight in 268 times when using distilled water. When salts are dissolved in the water, the polymer reduces its water abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
1
1
Order By: Relevance
“…The results showed that the substrate moisture for T2 was kept significantly higher than T0, and T1, despite receiving the same irrigation rate as T1 and a half of T0; however, this higher moisture availability in the substrate of T2 was not reflected in the plant's water status or growth. The higher water retention observed in the substrate with polyacrylamide gels was consistent with the information reported by the authors of [13], who pointed out that polyacrylamidebased polymers are highly absorbent and insoluble in water, a characteristic that allows one to increase the water-retention capacity in the soil and/or substrate. However, the difference observed in the water retention was not consistently reflected in the physiological parameters and biomass evaluated in the plants.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed that the substrate moisture for T2 was kept significantly higher than T0, and T1, despite receiving the same irrigation rate as T1 and a half of T0; however, this higher moisture availability in the substrate of T2 was not reflected in the plant's water status or growth. The higher water retention observed in the substrate with polyacrylamide gels was consistent with the information reported by the authors of [13], who pointed out that polyacrylamidebased polymers are highly absorbent and insoluble in water, a characteristic that allows one to increase the water-retention capacity in the soil and/or substrate. However, the difference observed in the water retention was not consistently reflected in the physiological parameters and biomass evaluated in the plants.…”
Section: Discussionsupporting
confidence: 90%
“…All these results do not coincide with what was observed by the authors of [10,12,13], who indicated that polymers favor the development of the crop. In our study, the hydrogel used demonstrated effective water retention, which is evidenced in the higher water content of the substrate compared to T1 and even T0 in some cases.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation